Low‐Loss Tunable Infrared Plasmons in the High‐Mobility Perovskite (Ba, La)SnO3. Issue 16 (13th March 2022) - Yang, Hongbin; Konečná, Andrea; Xu, Xianghan; Cheong, Sang‐Wook; Garfunkel, Eric; García de Abajo, F. Javier; Batson, Philip E.
Abstract: BaSnO3 exhibits the highest carrier mobility among perovskite oxides, making it ideal for oxide electronics. Collective charge carrier oscillations known as plasmons are expected to arise in this material, thus providing a tool to control the nanoscale optical field for optoelectronics applications. Here, the existence of relatively long‐lived plasmons supported by high‐mobility charge carriers in La‐doped BaSnO3 (BLSO) is demonstrated. By exploiting the high spatial and energy resolution of electron energy‐loss spectroscopy with a focused beam in a scanning transmission electron microscope, the dispersion, confinement ratio, and damping of infrared localized surface plasmons (LSPs) in BLSO nanoparticles are systematically investigated. It is found that LSPs in BLSO exhibit a high degree of spatial confinement compared to those sustained by noble metals and have relatively low losses and high quality factors with respect to other doped oxides. Further analysis clarifies the relation between plasmon damping and carrier mobility in BLSO. The results support the use of nanostructured degenerate semiconductors for plasmonic applications in the infrared region and establish a solid alternative to more traditional plasmonic materials. Abstract : High carrier mobility in perovskite BaSnO3 makes it a promising material for realizing high quality infrared plasmons. Here, low‐loss infrared plasmons with high confinement ratio are probed in La‐doped BaSnO3 nanorods by monochromated electron energy‐loss spectroscopy. The plasmon dispersion, damping, and loss mechanisms are systematically investigated at the single‐particle level and compared with traditional plasmonic materials.